Neuroprotective Potential and Memory Retention Effects Of Aegle Marmelos On Scopolamine-Induced Amnesia In Swiss Albino Mice - Sudheer, Akkiraju; Naveen, Rayadurgam; Vardhan, Kothamadhi Yuva; Saivamsi, Manapoti; Mounika, Mange Sai; Kumar, Tolisaku Pramod; Sravan sai, Jayaramappa (Journal of Neonatal Surgery, 2025)
Background: One major neurodegenerative disease that interferes with memory development is Alzheimer's disease (AD). Impaired encoding, consolidation, or retrieval of episodic memory is the cause of amnesia in early AD. Because of its anticholinergic properties, scopolamine mimics dementia by causing cognitive deficiencies. This study aimed to assesses the neuroprotective potential and memory retention effect of ethyl acetate fraction of Aegle marmelos (EFAM) scopolamine-induced amnesia in mice. Methods: EFAM (200 and 400 mg/kg, p.o.) was administered to Swiss albino mice for 30 days and scopolamine (3 mg/kg, i.p.) was injected to induce amnesia. Behavioural models such as elevated plus maze, hebb williams maze, and novel object recognition and biochemical indicators such as reduced glutathione and malondialdehyde were measured. Brain tissue histopathological analysis was also carried out. Results: Scopolamine-induced memory deficits were significantly restored by EFAM (200 mg/kg and 400 mg/kg) as indicated by decreased transfer latency (TL), time to reach the reward chamber (TRC) and increased recognition index (RI), and indicating an improvement in behavioural parameters. And also improved brain antioxidant defence (GSH, MDA levels), improved histopathological damage Conclusion: Based on the findings, this study suggests that EFAM may have a therapeutic function in the treatment of Alzheimer's disease by demonstrating neuroprotective potential against scopolamine-induced alzheimers through behavioral, biochemical, and histological changes